Occupational therapists: the quarterbacks of pelvic healthcare - Le Fevre, Eleanor, author; Schmid, Arlene, advisor; Weaver, Jen, committee member; Fruhauf, Christine, committee member (Colorado State University. Libraries, 2023)
Background: The ability to effectively manage chronic issues has a large impact on a person's quality of life. Pelvic floor dysfunction (PFD) is a chronic and debilitating disorder which affects millions of people worldwide. PFD is often placed lower in the hierarchy of treatable medical conditions yet has a substantial impact on a person's functional capability. Pelvic health occupational therapists (PHOT)s are emerging practitioners in PFD management. PHOTs provide a client-centred, holistic approach to care. To date PHOT is not well described in the literature or well known in the practice of pelvic healthcare. Aim: To investigate the perceptions of PHOTs, their value in the management of PFD, and how this value is communicated to other healthcare providers (OHCP)s. Methods: This qualitative research study included a demographic survey and one-to-one interviews with PHOTs and lead researchers. Thirteen PHOTs were interviewed by a lead researcher and provided data on their perceptions and interactions with OHCPs. Data collection was completed over a five-month period from July 2022-December 2022. Data collection ended once saturation in responses was reached. Data were analyzed by lead researchers using an in vivo coding process, creation of categories and code book. I created themes and sub-themes driven by the data. Results: Two main themes were created from the data with PHOT participants supporting inclusion of OT in pelvic healthcare; (1) pelvic healthcare is an interdisciplinary field; (2) more practitioners are needed in PHOT. Conclusion: PHOTs perceptions and value on interdisciplinary teams are key to increased communication between PHOTs, OHCPs, and the clients they serve. Further research is needed to define the PHOT role and impact as part of an interdisciplinary team.
Keywords: occupational therapy; pelvic health; pelvic floor; interdisciplinary